Sustainable Development of Corrosion Inhibitors from Electronic Scrap: Synthesis and Electrochemical Performance - J. Porcayo-Calderon; J.J. Ramos-Hernandez; E. Porcayo-Palafox; L.M. Martínez de la Escalera; J. Canto; J.G. Gonzalez-Rodriguez; L. Martinez-Gomez (Advances in Materials Science and Engineering)
Due to its high content of rare earths, the use of permanent magnets can be a sustainable alternative for the synthesis of environmentally friendly corrosion inhibitors in order to replace the use of highly toxic inhibitors, as well as the use of rare earth salts of high purity and high cost. In this study, the recovery of rare earths from permanent magnet wastes and their synthesis to chloride salts were carried out. Rare earth chlorides were evaluated as corrosion inhibitors by electrochemical techniques on API X70 steel in a 3.5% NaCl solution. Both anodic and cathodic polarization curves were made, and measurements of both open-circuit potential, linear polarization resistance, and electrochemical impedance were made. Results show that the inhibitor synthesized is a mixture of Nd and Pr chloride. Its performance as a corrosion inhibitor is superior to that of high purity Nd chloride (analytical reagent). The results show that the use of electronic scrap is a sustainable source for the synthesis of green corrosion inhibitors with low carbon footprint.